Study of Rock Physics and Seismic Attributes of Hydrocarbon Reservoirs in Sabah Basin - Anak Penguang, A.S. (Institute of Physics Publishing, 2017)
Elastic moduli are known to discriminate fluid and lithology for effective reservoir characterization. However, in some cases, the elastic modulus can also show the same response for different type of fluid and lithology. In our study area, a few elastic moduli were used to evaluate the hydrocarbon sands, water sand and shale as identified based on well log response. Seismic attributes such as Relative Acoustic Impedance attribute and RMS amplitude attribute are also applied to confirm the well log analysis and investigate the seismic response. Based on the results, the effective elastic moduli for our study area is the Lambda-Mu-Rho, Velocity Ratio (Vp/Vs), Poisson's ratio and Scaled Inverse Quality (Q) Ratio. The seismic attributes such as the Relative Acoustic Impedance highlights the impedance difference between the formations while RMS amplitude shows the hydrocarbon presence. The workflow of this study is applicable for other areas for effective fluid and lithology delineation. © Published under licence by IOP Publishing Ltd.